2022
DOI: 10.1007/s00344-022-10794-z
|View full text |Cite
|
Sign up to set email alerts
|

How Silicon Alleviates the Effect of Abiotic Stresses During Seed Germination: A Review

Abstract: Rapid synchronized seed germination is desirable to ensure seedling establishment and improve crop yield.However, abiotic stresses from drought, salinity, and heavy metals have a negative impact on seed germination.The application of silicon (Si) has emerged as a promising approach for improving seed germination, especially under unfavorable conditions. However, the mechanisms of Si action have not been systematically studied in germinating seeds under conditions of abiotic stress. Considering the potential im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 158 publications
0
3
0
Order By: Relevance
“…Plant hormones, such as gibberellic acid (GA) and abscisic acid (ABA), play pivotal roles in seed germination; GA activates hydrolytic enzymes, while ABA exerts an opposing influence. Water deficiency triggers an increase in ABA levels but a decrease in GA levels, thus failing to stimulate the synthesis of hydrolytic enzymes and impeding reserve mobilization [12][13][14]. Beyond hydrolytic enzyme activity, the activities of other enzymes such as α-amylase, β-amylase, and proteases are also adversely affected by water deficiency, further hindering seed reserve mobilization [15,16].…”
Section: Germinationmentioning
confidence: 99%
“…Plant hormones, such as gibberellic acid (GA) and abscisic acid (ABA), play pivotal roles in seed germination; GA activates hydrolytic enzymes, while ABA exerts an opposing influence. Water deficiency triggers an increase in ABA levels but a decrease in GA levels, thus failing to stimulate the synthesis of hydrolytic enzymes and impeding reserve mobilization [12][13][14]. Beyond hydrolytic enzyme activity, the activities of other enzymes such as α-amylase, β-amylase, and proteases are also adversely affected by water deficiency, further hindering seed reserve mobilization [15,16].…”
Section: Germinationmentioning
confidence: 99%
“…Nevertheless, studies on the use of preparations containing Si for treating seeds before sowing are rarely conducted on different species, e.g., cereals [ 29 ], vegetables [ 30 ], and legumes such as Medicago sativa [ 31 ]. According to the literature [ 32 ], the application of Si is a promising strategy to improve seed germination under abiotic stress conditions, but more specific research is needed on the use of this strategy in different crop species. Moreover, its effects on seed germination may depend on how the Si is applied.…”
Section: Introductionmentioning
confidence: 99%
“…Laboratory simulations of natural water shortage in the environment and the assessment of plant responses to drought during seed germination are possible thanks to the use of solutions with a negative potential (polyethylene glycol, PEG) [ 33 ]. Therefore, induced drought conditions are often used in such studies [ 10 , 32 ]. The knowledge of the optimal pH for plant seed germination is also important [ 34 ], especially in the case of species sown in mixtures on grasslands.…”
Section: Introductionmentioning
confidence: 99%
“…Among them is consideration of supplementation with silicon (Si), whose beneficial effects on plants subjected to biotic [ 19 , 20 ] and abiotic [ 21 ] stresses has been widely described in the literature. For example, a recent review reported that Si mitigates the negative effect of abiotic stresses as early as seed germination [ 22 ] and several studies have reported that Si supply enables alleviation of plants experiencing drought [ 23 ] or heat stress [ 24 ]. In the same way, a Si supply enables better tolerance to salt stress by sustaining various biological process such as photosynthesis or by stimulating detoxification of reactive oxygen species (ROS) [ 25 ].…”
Section: Introductionmentioning
confidence: 99%